Identifying and addressing underuse in hematologic care through systems-based hematology - Jacob C. Cogan; Allison E. Burnett; Alexandra Power-Hays; Geoffrey D. Barnes; Ming Y. Lim (Research and Practice in Thrombosis and Haemostasis)
Underuse of high-value hematologic care receives comparatively less attention than the overuse of unnecessary tests and treatments. In this review, we analyze examples of underutilized care in several domains: procedural (inferior vena cava filter retrieval), medical (hydroxyurea use in sickle cell anemia), and patient-facing (education prior to anticoagulation). For each, we justify the need for increased uptake and highlight examples of systems-based hematology interventions to accomplish this. While reducing overused care is appealing from a cost savings perspective, we advocate for equal attention and investment toward promoting underused care.